Time-dependent structure in the discharge rate of human motor units - Vaillancourt, David E.; Larsson, Lars; Newell, Karl M. (Clinical neurophysiology, 2002)
Objectives: The aim of this study was to examine the influence of visual and motor processes on the deterministic and stochastic structure of force output and motor unit discharge variability. Methods: Young adult subjects produced continuous, isometric force at 3, 6, 12, and 24% of their maximal voluntary contraction at low and high visual gain levels through abduction of the index finger. Force and fine-wire intramuscular electromyography were recorded. Results: There was a linear increase in discharge irregularity with increases in the mean motor unit discharge rate (8–30 Hz). Recurrence analysis showed that the percentage of deterministic structure in discharge variability remained high, but decreased linearly with increased motor unit discharge rate. Surrogate analyses confirmed that the motor unit discharge variability was inconsistent with an uncorrelated and linearly correlated Gaussian noise process. Spectral analysis revealed that both the force output and the mean time-varying motor unit discharge time series had a dominant frequency of 0–2 Hz. Visual feedback gain did not affect the individual motor unit discharge patterns. Conclusions: The motor unit discharge rate has deterministic time-dependent structure. The motor unit discharge rate is modulated at multiple time scales likely by pre- and post-synaptic induced fluctuations from spinal level pathways impinging on the motor neuron.